2020
DOI: 10.3329/bjog.v32i2.48277
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Weight Gain and its Relationship with Birth Weight of Baby at Term

Abstract: Background: Perinatal health is influenced by maternal weight gain. Increase in obesity in population and excess weight during pregnancy may be different complications including large for gestational age fetus. As a result cesarean delivery has increased in prevalence. Maternal weight gain during the 2nd and 3rd trimesters is an important determinant of fetal growth Objective: To determine the relationship between maternal weight gain and birth weight of baby at term. Methodology : A cross sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…A cross-sectional study of 50 pregnant women at term in Bangladesh showed that weight gain during pregnancy and maternal weight has emerged as the key factors influencing the birth weight of the baby. The study also found a direct relationship between maternal weight gain and foetal birth weight (Rijvi et al, 2017), as we have seen in our study.…”
Section: How Comparable Are Our Results With Other Studies?supporting
confidence: 91%
“…A cross-sectional study of 50 pregnant women at term in Bangladesh showed that weight gain during pregnancy and maternal weight has emerged as the key factors influencing the birth weight of the baby. The study also found a direct relationship between maternal weight gain and foetal birth weight (Rijvi et al, 2017), as we have seen in our study.…”
Section: How Comparable Are Our Results With Other Studies?supporting
confidence: 91%
“…In a similar study conducted in Bangladesh by Shiffin Rijvi et al only 4% of patients during pregnancy gained less than 5 kg of weight, the majority (68%) gained weight between 5 to 10 kg, whereas 28% gained weight over 10 kg. 16 In our study, 9.17% of newborns were born with low birth weight, 90.83% had normal birth weight and no newborn fell into the category of macrosomia. A cross-sectional study conducted by Janjua NZ in an urban population of Karachi found that the incidence of low birth weight was 18.5% which is almost double what we observed in our results.…”
Section: Discussionmentioning
confidence: 47%